Diagnostic Modalities Based on Flow Cytometry for Chronic Granulomatous Disease: A Multicenter Study in a Well-Defined Cohort - ÖZEN, AHMET OĞUZHAN; BARIŞ, HATİCE EZGİ; BARIŞ, SAFA (ELSEVIER, 2020)
BACKGROUND: Chronic granulomatous disease (CGD) is characterized by defective microbial killing due to mutations affecting subunits of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. Definitive genetic identification of disease subtypes may be delayed or not readily available. OBJECTIVE: Sought to investigate the role of intracellular staining of NADPH oxidase enzyme subunits in predicting the respective genetic defects in patients with CGD and carriers. METHODS: Thirty-four patients with genetically inherited CGD, including 12 patients with X-linked CGD (gp91(phagocyte oxidase (phox)) deficiency due to cytochrome b-245, beta polypeptide [CYBB] mutations) and 22 patients with autosomal-recessive CGD (p22(phox), p47(phox), and p67(phox) deficiency due to cytochrome b-245, alpha polypeptide [CYBA], neutrophil cytosolic factor 1 [NCF1] and NCF2 mutations, respectively) were recruited from different immunology centers and followed up prospectively. Dihydrorhodamine testing and NADPH oxidase subunit expression in white blood cells were determined by flow cytometry. RESULTS: gp91(phox) and p22(phox) defects, which result in simultaneous loss of both proteins due to their complex formation, were differentiated only by comparative analysis of patients' and mothers' intracellular staining. p47(phox) and p67(phox) protein expression was almost undetectable in patients compared with carrier mothers and healthy controls. The expression values of the respective subunits were found to be significantly higher in all controls as compared with carrier mothers, which in turn were higher than those of patients. CONCLUSIONS: Analysis of NADPH oxidase enzyme subunits by flow cytometry in patients and carriers is useful in the rapid prediction of the genetic defect of patients with CGD, thus guiding targeted sequencing and aiding in their early diagnosis. (C) 2020 American Academy of Allergy, Asthma & Immunology
Keywords: Chronic granulomatous disease; NADPH oxidase; flow cytometry; Dihydrorhodamine; gp91; p22; p47; p67; MUTATIONS; DIHYDRORHODAMINE; OXIDASE; ASSAY; FAMILIES; CARRIERS; TURKEY; BURST